Strategi Pengembangan Kawasan Terminal Majene Berbasis TOD (Transit Oriented Development) - Astinawaty, Astinawaty; Asriana, Zul (Universitas Sulawesi Barat, 2025)
The development of terminals as transportation hubs has an important and strategic role in growing the economy of urban areas. TOD (Transit Oriented Development) is a spatial planning concept that focuses on the development of transit areas around public transportation hubs such as train stations, bus terminal, or mass transportation stops including the Majene terminal. Based on BPS data, the increase in Majene terminal activity in the last five years was due to the high population (0,15%/year) and the number of motorized vehicles (26,7%/year). Several problems faced such as the status of terminal which has changed of its function, minimal of facilities, and infrastructure and the absence of attractions around the terminal area. This study aims to (1) to identify the suitability of the TOD concept in the Majene terminal area, (2) to formulate a TOD concept based on Majene terminal area development strategy which is identified through the regulation of Ministry of ATR BPN No. 16 of 2017 concerning the Development of Transit Areas.